Alcohol in Cerebrospinal Fluid (CSF) and Alcoholism - Agapejev, S. [UNESP]; Vassilieff, I. [UNESP]; Curi, P. R. [UNESP] (SAGE Publications, 1992)
Alcohol levels were measured in 15 cerebrospinal fluid (CSF) samples and 14 blood samples from grade III and I.V. male alcoholic patients with signs of nervous system involvement, and compared with levels detected in 11 CSF samples and 11 blood samples from abstemious patients or patients with grade I or I.I. alcoholism whose CSF had been found to be normal by routine analysis (controls). Among the alcoholic patients, alcohol levels were lower in the CSF than in blood, whereas the opposite was true for the controls. The possible mechanisms underlying this difference are discussed and the need for further study of this topic is emphasized. © 1992, Sage Publications. All rights reserved.